2000
DOI: 10.1038/sj.ejcn.1600963
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypertension in obese women. The role of weight cycling

Abstract: Objective: To study signi®cant factors associated with the risk of hypertension among obese women, with and without a history of weight cycling (WC). Design: Case ± control study. Setting: Obesity Clinic of Chieti University, Italy. Subjects: A group of 258 obese women aged 25 ± 64 y (103 cases with hypertension and 155 controls) were recruited. All obese subjects had the same clinical characteristics, were without a family history for hypertension, were non-smokers, had normal lipidemic pro®les and normal glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
2
32
0
3
Order By: Relevance
“…Consistent with other studies, we found no interaction between WF and weight change on the risk for MS or each MS component. 10,[31][32][33] There are a number of previous studies that have investigated the relationships between WF and each individual component of the MS. 10,[31][32][33][34][35][36][37] In our study, we found that WF had an increased risk for BP, HDL-c and WC. ORs for the fasting blood glucose and TG components followed the same trend and we assume that their nonsignificant results were related to insufficient statistical power (the number of cases was smaller than those for other components).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Consistent with other studies, we found no interaction between WF and weight change on the risk for MS or each MS component. 10,[31][32][33] There are a number of previous studies that have investigated the relationships between WF and each individual component of the MS. 10,[31][32][33][34][35][36][37] In our study, we found that WF had an increased risk for BP, HDL-c and WC. ORs for the fasting blood glucose and TG components followed the same trend and we assume that their nonsignificant results were related to insufficient statistical power (the number of cases was smaller than those for other components).…”
Section: Discussionsupporting
confidence: 51%
“…These results are in agreement with some previous analyses. WF over time was associated with an increased risk of hypertension in obese subjects in a study investigating the effect of short-term weight change using a 2-year weight cycling period 36 (results also confirmed with a 5-year period of WF estimation 34 ). WF was also associated with an increased body fat mass, BP and TG level in nonobese young women in an intervention study testing the effect of the succession of intentional weight cycling during a 6 months follow-up period.…”
Section: Discussionmentioning
confidence: 59%
“…26,27 Interestingly, a highly significant correlation between BMI and WHR was found only in weight cyclers but not among nonweight cyclers. 26 In contrast, no adverse effects of weight cycling on body fat distribution were found by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…18,25 It has been suggested that the adverse effects of weight cycling could be due to a redistribution of body fat to the upper body compartments. 26,27 In turn, an upper body obesity strengthens the risk of the 'Metabolic Syndrome', a constellation of metabolic diseases including dyslipidemia, insulin resistance, hypertension and its clinical consequences like cardiovascular disease and fatty liver. 1,2,28,29 Imaging techniques, that is, magnetic resonance imaging (MRI), computer tomography (CT) and dual-energy X-ray absorptiometry (DEXA), are precise and accurate techniques used to study lean body mass and adipose tissue distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] To our knowledge, the impact of short-term weight loss on the risk of hypertension has not been estimated in observational studies. With respect to the association between weight cycling and risk of hypertension, a positive relation was detected in a study group of obese women, 15 but no association was reported in a population of female nurses 13 and in a group of nonobese blue-collar workers. 16 The few studies examining weight cycling and risk of hypertension suggest differential effects of weight cycling depending on body weight status, in that weight cycling may present a risk factor for hypertension among obese subjects and may not influence the hypertension risk among non-obese people, but evidence is limited and requires further investigation.…”
Section: Introductionmentioning
confidence: 94%